2012
DOI: 10.1159/000339057
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 3 Activation Affects Serotonin Transporter Activity and Expression in Human Enterocyte-like Caco-2 Cells

Abstract: Serotonin, a neurotransmitter/autocrineagent mainly synthesized by intestinal enterochromaffin cells, regulates the whole intestinal physiology. Toll-like receptor 3 (TLR3) also contributes to the intestinal physiology by modulating intestinal innate immunity responses. Both serotonin and TLR3 are involved in intestinal inflammatory processes; however, the role of TLR3 in the regulation of intestinal 5-HT availability remains unexplored. The present study analyzes the effect of TLR3 activation on serotonin tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 41 publications
8
26
0
Order By: Relevance
“…The involvement of p38 MAPK in the regulation of SERT has been shown to be controversial; thus, in rat brain, p38 MAPK did not appear to affect SERT activity [46], and, in contrast, results in neural cells have suggested that p38 MAPK enhances SERT activity [47]. Our results agree with a previous study in intestinal epithelial cells, in which p38 MAPK activation seemed to mediate SERT activity inhibition [24]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The involvement of p38 MAPK in the regulation of SERT has been shown to be controversial; thus, in rat brain, p38 MAPK did not appear to affect SERT activity [46], and, in contrast, results in neural cells have suggested that p38 MAPK enhances SERT activity [47]. Our results agree with a previous study in intestinal epithelial cells, in which p38 MAPK activation seemed to mediate SERT activity inhibition [24]. …”
Section: Discussionsupporting
confidence: 88%
“…Recent results have suggested that TLRs may regulate the neuroendocrine activity of the intestinal epithelium [23, 24]. In relation to TLR2, previous results have shown that TLR2, TLR1 and TLR6 are co-expressed in human and mouse intestine and co-localize with 5-HT [25], suggesting a potential role for enteroendocrine cells in innate immune response through TLR activation.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that long-term NOD2 activation may decrease SERT expression via transcriptional and/or post-transcriptional mechanisms, offering an explanation for the 5-HT uptake reduction. In agreement with our results, other PRRs have also demonstrated inhibition of SERT activity with [21,22] or without [30] alteration of SERT expression. The activation of NOD2, with low concentrations of MPD, induces an inhibitory effect observed only in the short (30 minutes) and medium terms (6 hours), suggesting that a brief stimulation of NOD2 induces a rapid inhibition of SERT activity, increasing 5-HT extracellular availability to promote a fast inflammatory response.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a decrease in ileal TEER as early as 60 min after Poly(I:C) stimulation, an effect that cannot be entirely attributable to a specific cell type. Although we cannot rule out the contribution of Poly(I:C)-stimulated immune cells in our preparations, TLR-3 is also present in intestinal epithelial cells [23,24]. Therefore, it is possible that the responses observed were due to direct activation of TLR-3 bearing enterocytes rather than secondary to immune cell triggering.…”
Section: Discussionmentioning
confidence: 88%
“…Also, literature shows that Poly(I:C) induces effects in intestinal epithelial cells at concentrations varying from 600 ng/mL to 1 mg/mL [23,29,30]. In the present study a wide range of doses were tested but the highest dose (200 g/mL) was the only that consistently induced significant changes in Ussing chamber studies and everted gut sac assays; we then selected the in vivo dose (100 g/rat) based on these data.…”
Section: Discussionmentioning
confidence: 99%